Temporarily degraded physical properties of pyroclastic materials from Mount Semeru: Can they be improved after reclamation with vegetation and indigenous microbes? - Albarki, Georona Kusma; Sizilia, Vannya Julia; Kurniawan, Syahrul; Kusuma, Zaenal; Utami, Sri Rahayu (Journal of Degraded and Mining Lands Management, 2025)
The eruption of Mount Semeru in East Java released pyroclastic materials that damaged agroecosystems and degraded the soil physical properties. Pyroclastic materials tend to form surface crusts, leading to compaction and decreased permeability, which hinders soil recovery. To accelerate rehabilitation, adaptive vegetation and indigenous microbes were introduced to improve the physical properties of pyroclastic materials. This study aimed to assess the incorporation of indigenous microbes and adaptive vegetation in improving soil quality after an eruption. This study employed a factorial randomized complete block design with two factors: vegetation type, i.e., Napier grass (Vn), Centrosema sp. (Vc), and Indigofera sp. (Vi); and microbial application, i.e., without microbes (M0) and with indigenous microbes (M1). Soil bulk density, total porosity, permeability, available water content, and evapotranspiration were measured. The data were analyzed using ANOVA and LSD at 5% significance level, followed by regression and correlation analysis. The results showed that incorporating indigenous microbes with adaptive vegetation significantly increased total porosity, permeability, and available water content while decreasing bulk density and evapotranspiration. Specifically, the Napier grass with microbe treatment (VnM1) was most effective in reducing compaction, attributed to its extensive root system and enhanced microbial activity. This treatment improved water retention and provided a sustainable solution for rehabilitating pyroclastic materials, supporting long-term agricultural recovery after the eruption.